The Role of the State in Health Law Enforcement in Indonesia: A Constitutional Law Perspective - S.T. Kansil, Christine; Ulataqiy, Adifa Jauza (CV. Rayyan Dwi Bharata, 2024)
The role of the state in enforcing health law in Indonesia is a crucial aspect aligned with constitutional provisions, particularly Article 28H paragraph (1) of the 1945 Constitution, which emphasizes the right to health. The state is expected to create a legal system that protects and fulfills the health rights of the community through the formulation of policies, regulations, and oversight of health service delivery. The implementation of Law No. 36 of 2009 on Health underscores the government's responsibility to provide accessible and quality health services. Health law enforcement includes actions against violations, including sanctions for providers that do not comply with standards. In this context, the state must also respond to health emergencies, such as pandemics, with swift and effective measures. Additionally, public participation in health decision-making processes is vital. In the long term, political commitment and adequate resource allocation are necessary to ensure the sustainability of health programs. Through a holistic, human rights-based approach, the state can create an inclusive and quality health system for all members of society.